Legendary artists and the clothes they wore - Newman, Terry (Fashion journalist) (Harper Design, an imprint of Harper Collins Publishers, 2019)
Profiles more than forty iconic artists in relationship to their sartorial choices. A compelling mix of anecdotes, portraits of the artists in their studios, art and runway imagery, and commentary by critics, designers, and the artists.